Sub-1 GHz Wireless Nodes Performance Evaluation for Intelligent Greenhouse System - I Nyoman Kusuma Wardana; Ngakan Nyoman Kutha Krisnawijaya; I Wayan Aditya Suranata (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
Greenhouses provide not only solution to problems faced by conventional farming systems but also play an important role to improve the energy efficiency and environmentally friendly awareness. To achieve benefits of greenhouse farming system in terms of energy efficiency, research related to this issue have been done by many researchers. However, resources that concern on how to practically implement the particular energy-saving technology for greenhouses need to be improved. In this research, field experiment results related to low-power communication between nodes have been reported by implementing universal prototype modules. The pros and cons of existing communication technology, the proposed architecture of network and module analysis, and the performance evaluation of the proposed module dedicated to intelligent greenhouse farming system were also discussed.